Answer:
3 lol
Step-by-step explanation:
Answer:
A. 23+(6-1)x-3
B. 93
Step-by-step explanation:
a) Nth term = F + (N - 1) x D, where F=First term, N=Number of terms, D=Common difference
6th row = 23 + (6 - 1) x -3
= 23 + (5) x -3
= 23 + (-15)
= 8 - number of boxes in the top row.
b) Sum = N/2[2F + (N - 1) x D]
= 6/2[2*23 + (6 - 1) x -3]
= 3 [46 + (5) x -3 ]
= 3 [46 + -15 ]
= 3 [ 31 ]
= 93 - total number of boxes in the entire display.
Hope this helps! Its 3:25 AM for me too so I know how you feel.
4/12 is less than 4/6
4/12 = 2/6
and 2/6 < 4/6
You first need to cross multiply to get 8x+8=6x^2-6. Then make the function into 6x^2-8x-14=0 which can be simplified into 3x^2-4x-7=0 by dividing the equation by 2. Then you must split the middle(-4x) to get 3x^2+3x-7x-7=0. This simplifies to 3x(x+1)-7(x+1)=0 and then to (3x-7)(x+1)=0. From here you just solve for each root which you will find are x= -1 and 7/3
Answer:
The unknown number is -5.
Step-by-step explanation:
-3 + -5 = -8
-8 - -3 = -5
-8 - -5 = -3